Reporting verb in research projects of EFL English major students - CHATTRAPORN JUNNAK; ANCHALEE VEERACHAISANTIKUL (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: The current study set out to determine 1) which types of reporting verbs are most commonly used by EFL English major students in their research projects and 2) which types of reporting verbs are most commonly used by this population.Method: 52 research projects written by English as a Foreign Language (EFL) students majoring in English were chosen and analyzed to achieve the study’s goals. Furthermore, reporting verbs were categorized according to Francis, Huston, and Manning’s (1996) work.Findings: As the results indicated,